Service users’ experiences of multi-agency practice in children’s social care: the Common Assessment Framework - Lucas, Steven (2016)
This thesis examines the agency and experience of children, young people, and their parents, participating in multi-agency assessment in a children’s services early intervention process. The Common Assessment Framework (CAF) was introduced as a national pilot and widely adopted in England in the past decade. Research has examined the professional practice and systemic factors around the implementation of the CAF, but there is very little investigation of service users’ experiences that considers the agency and perspectives of service users as partners in the process of early help. This qualitative study was accomplished in one local authority site in the midlands of England, where 12 families, including 7 young people and 16 carers, were interviewed. To explore service users’ experiences of multi-agency working, semi-structured interview schedules and free drawn charts and graphs of CAF activity were employed. In order to make sense of service users’ agency and participation in this setting, a methodological approach informed by actor-network theory and Foucauldian governmentality, was adopted. The empirical findings of the research demonstrated the relative exclusion of children and young people from the main elements of the CAF process. This lack of active participation is analysed as a response to the prevailing model of childhood as an incompetent and vulnerable stage of ‘becoming adult’. The participation of adults in the CAF was found to engage a more active human agency, although a diverse range of experiences was found. Parents, who responded to a perceived ’bad parent’ critique from practitioners, assembled a heterogeneous set of actors, including discourse, knowledge from service user sources, and personal skills in working with different organisations, in order to construct an active service users’ identity. The thesis concludes with reflection on service users’ agency and participation and makes some policy recommendations and suggestions for further research.